A Mathematical Model for Internal Task Scheduling in Cross Docking - D. Buakum (2020)
© 2019 IEEE. This study proposes a novel problem for solving task scheduling in cross docking. In particular, we formulate a mathematical model for the task scheduling between inbound and outbound dock doors in order to minimize total operational time based on limited resource. The goal is to determine the start time and finish time of each operation on the assigned working team and transfer equipment with respect to maximum resource utilization. The use of mathematical model is paving the way to Artificial Intelligence (AI) for smart decision in cross docking since AI is a key factor in Industries 4.0. Moreover, facility cost is analyzed based on trade-off features between cost and makespan so that a decision can be made based on a decision maker's preference.